THE INFLUENCING OF MEDIA SENTENCE BUILDING GRID TO THE INCREASING WRITING ABILITY ON MIDWIFERY COLLEGERS AT STIK BINA HUSADA PALEMBANG - Samaya, Doni (UNIVERSITAS TRIDINANTI PALEMBANG, 2018)
ABSTRACT : The aim of this research is to describe the moral values of the novel Kado untuk Putri Ungu written by Syamsa Hawa. The subject of this study is the novel Kado untuk Putri Ungu written by Syamsa Hawa and object of this study is moral values of Kado untuk Putri Ungu written by Syamsa Hawa. The data collection is documentation. The results of documentation is analyzed by using descriptive qualitative method. Based on the results of this research, the researcher found out that novel Kado untuk Putri Ungu written by Syamsa Hawa contained the moral values as follows: 1) the relationship between human and herself, 2) the relationship between human and human, 3) the relationship between human and God. Keywords: moral values, novel, Kado untuk Putri Ungu.